Decoding of Emotional Components in Complex Communicative Situations (Irony) and Its Relation to Empathic Abilities in Male Chronic Alcoholics: An Issue for Treatment. (8th November 2012) - Amenta, Simona; Noël, Xavier; Verbanck, Paul; Campanella, Salvatore
<x xml:space="preserve">Abstract</x> Background Previous research has shown that deficits in the domain of emotions strongly characterize alcoholism. Patients diagnosed with alcoholism show impairments in emotional mimic recognition, as well as in the domain of emotional prosody. These data suggest that male alcoholics might suffer from a generalized emotional impairment associated with dysfunctions in empathy. Taken altogether, those deficits might influence alcoholics' relational domain and their performance in complex communicative situations such as ironic interactions. The present study investigates the ability of chronic male alcoholics to recognize the emotional component of ironic contexts and its relation to the comprehension of ironic meaning as a function of their empathic abilities. Methods Forty‐four male subjects participated in a story comprehension task. They were asked to read stories with either an ironic or a nonironic ending. Participants were asked to fill in a questionnaire about communicative intentions and the emotional states of the stories' characters. Moreover, the correct comprehension of the ironic meaning was assessed through a self‐reported questionnaire and related to the empathy quotient (EQ) which was measured in a preexperimental phase. Results Alcoholic subjects showed a lower EQ in comparison to healthy subjects and recognized significant fewer ironic endings. Social skills results were particularly impaired. The correlation between EQ and ironic endings recognition was significant. Moreover, alcoholics showed a tendency to attribute positive emotions to both ironic and nonironic contexts, showing an opposite pattern in comparison with control subjects who tended to associate negative emotions to ironic contexts. Conclusions The present study indicates that emotional recognition deficits that have been previously observed in chronic alcoholics extend to complex interactive contexts. This deficit is associated with a more general impairment of empathy, especially in its social skill component. Clinical implications of the present results are discussed.